Correlation between Quantitative HBsAg and HBV-DNA in Chronic Hepatitis B Infection - Putu Prathiwi Primadharsini; I Dewa Nyoman Wibawa (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Background: Methods used to diagnose and monitor chronic hepatitis B (CHB) by quantitation of hepatitis B virus-deoxyribonucleic acid (HBV-DNA) levels is expensive. Cheaper laboratory test as an additional markeris needed, thus we studied serum quantitative HBsAg to be used as surrogate marker in CHB patients. This study was aimed to investigate correlation between serum quantitative HBsAg and HBV-DNA in CHB patients.Method: In this cross-sectional study, we enrolled 62 CHB patients between January 2010 and December 2012 who had quantitative HBsAg and HBV-DNA assays in a private laboratory at Denpasar. HBV-DNA was measured by real-time polymerase chain reaction and quantitative serum HBsAg was measured by chemiluminescent microparticle immunoassay (CMIA). Stastistical analysis was performed by Mann-Whitney and Spearman’s correlation.Results: Of 62 patients, most subjects were males (82.26%). Mean HBsAg titer of CHB in HBeAg positive and negative patients were 281,000 and 4,900 IU/mL, respectively; while mean HBV-DNA in HBeAg positiveand negative patients were 59,000,000 and 7,530,000 IU/mL, respectively. We found that quantitative HBsAg and HBV-DNA in HBeAg positive and HBeAg negative patients were statistically signi cant (p = 0.0001, p = 0.0001, respectively). Signi cant correlation was found between serum quantitative HBsAg and HBV-DNA (r = 0.737; p= 0.000). Quantitative HBsAg was signi cantly correlated with HBV-DNA in HBeAg-positive subgroup (r = 0.717; p = 0.0001); and signi cant correlation was also found in HBeAg-negative subgroup (r = 0.443; p = 0.006) although the correlation was weak. Conclusion: Quantitative HBsAg has signi cant correlation with HBV-DNA in CHB patients. Keywords: quantitative HBsAg Assay, HBV-DNA, HBeAg, chronic hepatitis B infection